Visual similarity effects in immediate serial recall and (sometimes) in immediate serial recognition. - Chubala, Chrissy M.; Guitard, Dominic; Neath, Ian; Saint-Aubin, Jean; Surprenant, Aimée M. (Memory & Cognition, 2020)
Words that sound dissimilar are recalled better than otherwise comparable words that sound similar on both immediate serial recall and immediate serial recognition tests, the so-called acoustic similarity effect. Although studies using immediate serial recall have shown an analogous visual similarity effect, in which words that look dissimilar are recalled better than words that look similar, this effect has not been examined in immediate serial recognition. We derived a prediction from the Feature Model that a visual similarity effect will be observed in immediate serial recognition only when the items are acoustically dissimilar; the model predicts no effect when the items are acoustically similar. Experiments 1 and 2 used visually dissimilar and visually similar stimuli that were all acoustically similar and replicated the visual similarity effect in serial recall but revealed no effect in serial recognition. Experiments 3 and 4 used a second set of stimuli that were acoustically dissimilar and found a visual similarity effect in both serial recall and serial recognition. The experiments confirm the Feature Model's predictions and add to earlier findings that the two tests, serial recall and serial recognition, may show quite different results because the two tests are not as similar as previously thought.